Improvement of organic field-effect transistor characteristics via oxidation treatment of Ag nano-ink electrode surfaces. (28th November 2019) - Minagawa, Masahiro; Kobayashi, Kanta; Sone, Shinnosuke; Shinbo, Kazunari
Abstract: Organic field-effect transistors (OFETs) containing surface oxidized Ag nano-ink electrodes were fabricated in order to investigate their electrical properties. OFETs having gate electrode/n-type Si wafer/SiO2 treated with octadecyltrichlorosilane/Ag nano-ink source–drain electrodes/deposited 9, 10-diphenylanthracene (DPA) layer stacked structures were fabricated. The silver nano-ink electrodes were oxidized by exposure to ultraviolet light (184.9 and 253.7 nm) before DPA-layer deposition. The OFETs having unoxidized electrodes failed to operate, while the drain currents of the OFETs with oxidized electrodes increased with oxidation time. The largest drain current (−269  μ A) was obtained for the OFET with an electrode oxidation time of 600 s, which resulted in a reduction in the contact resistance to 9.5 kΩ cm despite the large ionization potential of the DPA layer (∼5.8 eV). The observed behavior is attributed to the oxidized Ag electrodes enhancing hole injection by oxidizing the surface of the DPA layer.